Effects of Aerobic Exercise on Metabolic Syndrome, Cardiorespiratory Fitness, and Symptoms in Schizophrenia Include Decreased Mortality - Schmitt, Andrea; Maurus, Isabel; Rossner, Moritz J.; Röh, Astrid; Lembeck, Moritz; von Wilmsdorff, Martina; Takahashi, Shun; Rauchmann, Boris; Keeser, Daniel; Hasan, Alkomiet; Malchow, Berend; Falkai, Peter (Frontiers in Psychiatry, 2018)
Schizophrenia is a severe psychiatric disorder with a lifetime prevalence of about 1%. People with schizophrenia have a fourfold higher prevalence of metabolic syndrome than the general population, mainly because of antipsychotic treatment but perhaps also because of decreased physical activity. Metabolic syndrome is a risk factor for cardiovascular diseases, and the risk of these diseases is two- to threefold higher in schizophrenia patients than in the general population. The suicide risk is also higher in schizophrenia, partly as a result of depression, positive and cognitive symptoms of the disease. The higher suicide rate and higher rate of cardiac mortality, a consequence of the increased prevalance of cardiovascular diseases, contribute to the reduced life expectancy, which is up to 20 years lower than in the general population. Regular physical activity, especially in combination with psychosocial and dietary interventions, can improve parameters of the metabolic syndrome and cardiorespiratory fitness. Furthermore, aerobic exercise has been shown to improve cognitive deficits; total symptom severity, including positive and negative symptoms; depression; quality of life; and global functioning. High-intensity interval endurance training is a feasible and effective way to improve cardiorespiratory fitness and metabolic parameters and has been established as such in somatic disorders. It may have more beneficial effects on the metabolic state than more moderate and continuous endurance training methods, but to date it has not been investigated in schizophrenia patients in controlled, randomized trials. This review discusses physical training methods to improve cardiorespiratory fitness and reduce metabolic syndrome risk factors and symptoms in schizophrenia patients. The results of studies and future high-quality clinical trials are expected to lead to the development of an evidence-based physical training program for patients that includes practical recommendations, such as the optimal length and type of aerobic exercise programs and the ideal combination of exercise, psychoeducation, and individual weight management sessions.